Developing a Diagnostic Test of Critical Thinking Skills In Physics Lessons - AM, Muh. Asriadi; Hadi, Samsul (Universitas Negeri Semarang, 2023)
A diagnostic test of critical thinking ability is a method to reveal the location of students' weaknesses and strengths in critical thinking skills, especially in physics subjects. This study aims to develop a diagnostic test of quality critical thinking skills in physics subjects regarding validity and reliability and the quality of items in diagnosing students' critical thinking skills. This research is development research whose development procedure uses a combination of the Ministry of National Education development model (2007) with the test development procedure from Mardapi (2017), which consists of 11 steps, namely: (1) identifying essential competencies that have not been completed, (2) determining possible root causes of problems, (3) developing test specifications, (4) writing tests, (5) assessing tests by experts, (6) conducting test trials, (7) analyzing the quality of test items, (8) ) improving tests, ( 9) assembling test, (10) conducting the test, (11) interpreting the test result. The subjects of this study were MAN students in the city of Yogyakarta. Data were analyzed by CVR, EFA, and PCM tests. The results showed that the diagnostic test model for critical thinking skills was valid, reliable, and had good item quality in diagnosing students' critical thinking skills. The diagnostic test results show that MAN students' critical thinking ability in the city of Yogyakarta in physics subjects is more dominant in the low category with a percentage of 35.30%. As a result of knowing the description of students' critical thinking weaknesses, the findings of this study can be used as a reference, particularly for physics teachers, to improve the quality of physics learning.